2021
DOI: 10.1080/15376494.2021.1937758
|View full text |Cite
|
Sign up to set email alerts
|

Topological surface wave metamaterials for robust vibration attenuation and energy harvesting

Abstract: Metamaterials are extensively utilized to manipulate ground surface waves for vibration isolation within the bandgap frequency ranges whereas topological crystals allow the creation of robust edge states immune to scattering by defects. In this work, we propose a topological surface wave metamaterial working in the Hertz frequency range, constituted of triangle shape concrete pillars arranged in a honeycomb lattice and deposited on the soil ground. Based on the analogue of quantum valley Hall effect, a non-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 52 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The multifaceted capabilities of the proposed 3D metamaterial could help to improve performance in engineering applications that involve low‐frequency and multiband elastic wave control, such as vibration energy harvesters and isolators. [ 10 , 11 , 12 , 13 , 14 , 51 , 52 ] Moreover, the rich 3D, multiband, frequency‐dependent, and polarization‐dependent features of the metamaterial could be utilized to construct information‐dense phononic circuitry (i.e., elastic wave‐based, with information‐density derived from the three distinct elastic wave polarizations: two quasi‐shear and one quasi‐longitudinal) for mechanical computers, wave filters, and on‐chip devices. [ 15 , 16 , 17 , 18 , 19 , 74 ] For example, the proposed metamaterial may be used as the building block of 3D phononic circuits with multiple working channels that route waves in a layer‐dependent fashion based on the polarization and frequency of external inputs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multifaceted capabilities of the proposed 3D metamaterial could help to improve performance in engineering applications that involve low‐frequency and multiband elastic wave control, such as vibration energy harvesters and isolators. [ 10 , 11 , 12 , 13 , 14 , 51 , 52 ] Moreover, the rich 3D, multiband, frequency‐dependent, and polarization‐dependent features of the metamaterial could be utilized to construct information‐dense phononic circuitry (i.e., elastic wave‐based, with information‐density derived from the three distinct elastic wave polarizations: two quasi‐shear and one quasi‐longitudinal) for mechanical computers, wave filters, and on‐chip devices. [ 15 , 16 , 17 , 18 , 19 , 74 ] For example, the proposed metamaterial may be used as the building block of 3D phononic circuits with multiple working channels that route waves in a layer‐dependent fashion based on the polarization and frequency of external inputs.…”
Section: Discussionmentioning
confidence: 99%
“…These so-called topological metamaterials enable low-loss transport and arbitrary directional manipulation of elastic waves via localized topological states that are protected from unwanted scattering in the presence of structural defects or disorder. [5][6][7][8][9] The remarkable capabilities and robustness of topological metamaterials have been exploited to enhance performance in technical applications that include vibration energy harvesters [10][11][12][13][14] and a mechanical information processor, [15] and have additionally inspired investigations on their potential implementation in on-chip devices [16][17][18][19] and elastic antennas. [20] Initial research concerning topological metamaterials focused on the theoretical prediction and experimental demonstration of 0D topological states in 1D mechanical structures (e.g., the wave is localized at a point in a rod) and 1D topological states in 2D mechanical structures (e.g., the wave is localized along a line waveguide in a thin plate).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou & Wan [24] proposed a new type of metamaterial with high efficiency on Rayleigh wave isolation. Besides, topology has also been introduced to the study of the performance of metamaterials on surface waves [25]. The experimental research further confirmed the value of PWBs in engineering applications [26].…”
Section: Introductionmentioning
confidence: 98%
“…In order to address this issue of several redundant piezo-electric materials, the concept of edge state diatomic periodic chain is introduced in this paper. Edge-state metamaterials localize the energy at the point of asymmetry and the band transition mechanism gives rise to the existence of interface mode (Chen et al, 2018;Ni and Shi, 2022;Pal et al, 2018Pal et al, , 2019Wu et al, 2021b). Analysis of this phenomena is widely studied in relation to topological insulators (Darabi and Leamy, 2019;Xia et al, 2017) and wave guides (Ma et al, 2018;Miniaci and Pal, 2021;Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%